Instructional systems design today and in the future - Emerson, Tricia; American Society for Training and Development; Stewart, Mary; American Society for Training and Development; Institute for Corporate Productivity; Books24x7, Inc (An ASTD research study, 2010)
The Change Book provides a practical collection of tips and advice for anyone dealing with or managing organizational change. You will learn about change management, how to plan for change, how to create a communication strategy, and more. While not a comprehensive guide to leading change, this concise book contains an array of useful insights for change managers and is a great resource for people new to the concept or change.
Keywords: Instructional systems : Design; Strategic planning; Organizational change; Education; Social Sciences; Theory & Practice of Education